Human factors in aviation and aerospace - Keebler, Joseph R.; Lazzara, Elizabeth; Wilson, Katherine A.; Blickensderfer, Elizabeth L. (Academic Press, 2023)
"The third edition of Human Factors in Aviation and Aerospace is a fully updated and expanded version of the highly successful second edition. Written for the widespread aviation community including students, engineers, scientists, pilots, managers, government personnel, etc., this edition continues to offer a comprehensive overview, including pilot performance, human factors in aircraft design, and vehicles and systems. With new editors, this edition adds chapters on aviator attention and perception, accident investigations, automated systems in civil transport airplanes, and aerospace. Multicontributed by leading professionals in the field, this book is the ultimate resource for anyone in the aviation and aerospace industries."-- Provided by publisher.
Keywords: Aeronautics -- Human factors.; elektronické knihy; electronic books